Analisis Metode Penelitian Tindakan Kelas (PTK) dalam Peningkatan Kualitas Pembelajaran di Sekolah: Penelitian - Jessica Tri Agustin; Desy Eka Citra Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Efforts to improve the quality of education require continuous improvement in the quality of learning in schools. Classroom Action Research (CAR) is an effective strategy for addressing various learning issues, such as low student participation, lack of teacher innovation, and weak teaching method effectiveness. This research used a qualitative descriptive approach with a literature review method. The results of the study indicate that CAR has a significant contribution to improving learning practices through a continuous cycle of action and reflection. The implementation of CAR has been proven to increase student participation, strengthen teacher professionalism, and have a significant impact on learning outcomes. In addition, CAR makes teachers more reflective and innovative in managing learning.